SUPPORTED CONSTRUCTION FOR QUARRY EXCAVATOR TRAVERS - Orysenko, O. V.; Fenko, O. G.; Zotsenko, М. L.; Vynnykov, Yu. L.; Kharchenko, М. O. (Academic journal Industrial Machine Building Civil Engineering, 2018)
It has been established that repair of quarry excavators should be carried out directly on site. In this case, the use of jacks for weighing the rotary platform of excavators Bucyrus RH340 and Terex RH200 models for repair of running equipment is impossible because of their design features. This type of repair is suggested to be performed as an excavator based on the design developed by the authors. The installation of the excavator on the support structure is carried out by its working equipment. The supporting structure is suggested to be made in the form of two identical fragments for its unification regarding the base of excavators and the convenience of transporting to the site of work. The suugested method of fixing the excavator to the support structure prevents it from being displaced from the impact of seismic loads during blasting operations. The investigation of the stress-strain state of the supporting structure was carried out using the complex of finite-element analysis.